Impaired activation of ALS monocytes by exosomes - Zondler, Lisa; Feiler, Marisa S.; Freischmidt, Axel; Ruf, Wolfgang P.; Ludolph, Albert C.; Danzer, Karin M.; Weishaupt, Jochen H. (Immunology & cell biology, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal and progressive neurodegenerative disease affecting predominantly motor neurons in the spinal cord and motor cortex. Neurodegeneration in ALS is accompanied by a well-characterized neuroinflammatory reaction within the central nervous system and, as described more recently, cells of the peripheral immune system. Particularly monocytes have been implicated in ALS pathogenesis. Exosomes are membrane-enclosed vesicles secreted by various cell types with a diameter of 50-150 nm. Circulating blood exosomes have been shown to be important mediators and regulators of immunity. Therefore, we hypothesize that circulating blood exosomes are putative mediators of monocytic deregulation in ALS. Here we characterize exosomal uptake and the respective immunological reaction of peripheral monocytes from ALS patients and healthy donors using both serum-derived exosomes and TDP-43-loaded exosomes produced in cell culture. We found the pro-inflammatory cytokine secretion by ALS monocytes upon exosomal stimulation to be impaired compared with control monocytes. Moreover, we demonstrate that exosomal TDP-43 induces increased monocytic activation compared with non-aggregation-prone cargo. Therefore, this study underlines the functional deregulation of ALS monocytes and the impact of circulating blood exosomes on monocyte activation.
Zuerst veröffentlicht: 04 October 2016
Gesehen am 08.07.2021